The EU ETS Up to 2030 : Decoding Auctioning Challenges for Romania - World Bank (Washington, DC, 2016)
This report presents some figures exploring the way Romanian installations have been operating under the European Union Emissions Trading System (EU ETS). At the request of the Government of Romania, a two-year Reimbursable Advisory Services (RAS) Program on climate change and low-carbon green growth was launched by the World Bank in July 2013. The RAS project focuses on operationalizing Romania’s national climate change strategy and action plan, identifying and integrating climate-related actions in new operational programs, building a solid analytical base for impact assessments and climate-related decision making, and enhancing climate-friendly practices and monitoring systems. Component D aims at supporting the Government institutions in implementing, monitoring, and evaluating climate change actions and sharing their experiences. In this context, the present report provides a background overview and analysis on EU Emissions Trading System (EU ETS) in general, as well as on the participation and compliance of Romanian EU ETS installations. A number of ETSs have been implemented to curb air pollution, in particular greenhouse gas (GHG) emissions, in order to mitigate climate change. The EU ETS was proposed in 2001 by the European Commission to help EU countries meet their national commitments under the Kyoto Protocol. The choices in the allocation process made by European Member States since the inception of the EU ETS in 2005 have modified the way the “carbon rent” created through allocation is distributed among economic players, industries, utilities, but also governments and indirectly citizens and tax payers. In parallel, European governments have committed to report on their use of auction revenues and to dedicate at least half of them to climate-related policies. In particular, the changes in the allocation process raise questions regarding their impact on European competitiveness. Because European industries are already fighting to keep market shares on the international market, it is often feared that an additional constraint, through carbon pricing, would make their playing field even less leveled. Member States thus have to consider a number of parameters in their use of auction revenues.